2009
DOI: 10.1088/0957-4484/20/24/245707
|View full text |Cite
|
Sign up to set email alerts
|

Amplified spontaneous emission in polymer–CdSe/ZnS-nanocrystal DFB structures produced by the holographic method

Abstract: Amplified spontaneous emission (ASE) is demonstrated in volume-distributed feedback (DFB) structures, formed by colloidal CdSe/ZnS nanocrystals and ZrO2 nanoparticles (NPs) in a polymer matrix. Periodic redistribution of the NPs in an organic matrix was carried out by holographic photopolymerization in a specially developed light-sensitive nanocomposite. The composite consists of two acrylate monomers and two types of inorganic NPs. The NPs provide for the formation of two co-phased gratings-a refractive index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 39 publications
(69 reference statements)
0
34
0
Order By: Relevance
“…Therefore, a polymer nanocomposite containing semiconductor nanocrystals results a flexible material which joins the active properties of the nanoparticles together with the technological feasibilities of the polymer matrices [4,76]. For example, a DFB grating fabricated on polymers containing CdSe/ZnS QDs have been proposed to demonstrate lasing [80,81], even under nanosecond excitation [81].…”
Section: Polymer Nanocompositesmentioning
confidence: 99%
“…Therefore, a polymer nanocomposite containing semiconductor nanocrystals results a flexible material which joins the active properties of the nanoparticles together with the technological feasibilities of the polymer matrices [4,76]. For example, a DFB grating fabricated on polymers containing CdSe/ZnS QDs have been proposed to demonstrate lasing [80,81], even under nanosecond excitation [81].…”
Section: Polymer Nanocompositesmentioning
confidence: 99%
“…Nanoparticles with a photothermal effect, such as gold nanoparticles (AuNPs) and CNT, are used for NIR-driven drug release. (Reproduced from [54], [69]- [71], [87], [98], [112], and [121].) for biomedical usage, by successfully implanting them into rabbit eyes without significant biological damage, as shown in Fig.…”
Section: A Refraction Index Modulation With Nanoparticlesmentioning
confidence: 99%
“…Smirnova and coworkers encapsulated CdSe/ZnS nanocrystals and ZrO2 NPs and prepared distributed feedback (DFB) structures by holographic lithography [112]. In doing so, they achieved amplified spontaneous emission, and proved that a DFB structure composed of QDs confined in polymer matrix displays enhanced light emission intensity and a narrower peak width (shown in Fig.…”
Section: Optical Application Of Nanocomposites Using Absorption Prmentioning
confidence: 99%
“…The lightemissive high RI NP can provide optical feedback and serve as a gain medium at the same time. We have shown that the DFB-cavities based on polymer grating doped emissive CdSe/ZnS quantum dots as a gain medium and containing ZrO 2 NP to enhance the feedback efficiency perform a sharp amplified spontaneous emission (ASE) by pumping with fs Ti-sapphire laser pulses [26].…”
Section: Holographic Nanocomposites Containing Low Ri and Metal Npmentioning
confidence: 99%